Innovation Strategies for Defence: The Successful Case of Defence Medical Services. Issue 2 (4th March 2017) - Ford, Matthew; Hodgetts, Timothy; Williams, David
Abstract : Over the past 20 years, the Defence Medical Services (DMS, the umbrella organisation for medical provision within the British armed forces) has been innovating consistently and at pace within the Ministry of Defence. The result of this sustained effort has led to progressive improvement in the outcomes of the critically injured. Separately, it has also led to global transformational innovation in support of the response to the Ebola epidemic in Sierra Leone. Through planned and orchestrated interventions across the entire organisation, from leadership to technology, medical practices to training and organisational design, the DMS can legitimately claim to have achieved a 'Revolution in Military Medical Affairs'. Matthew Ford, Timothy Hodgetts and David Williams examine the innovation lifecycle within the DMS as it defines its response to the challenges of the changing character of conflict and consider the way defence medicine is an example to the wider military.